PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA JENEBERANG IKKBORONGLOE DI KABUPATEN GOWA - Pradhita Udayani; Haeruddin, M. Ikhwan Maulana; Zainal Ruma (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of service quality partially and simultaneously on customer satisfaction. The type of research used is descriptive quantitative with 100 respondents for sampel. The population in this study are active customers of PDAM Tirta Jeneberang IKK Borongloe in Gowa Regency. Data collection techniques using observation techniques, questionnaires and literature study. The data analysis technique used multiple linear regression test. The results showed that based on the partial test of direct evidence, reliability, responsiveness, assurance and empathy variables has a significant effect on customer satisfaction. On the simultaneous testing of each service quality indicator (direct evidence, reliability, responsiveness, assurance and empathy) has a significant effect on customer satisfaction.